Treatment seeking behavior among patients with polycystic ovarian syndrome (PCOS)-A cross-sectional study from Northern India - Ishwarpreet Kaur; Amarjeet Singh; Vanita Suri; Kamal Kishore; Satya Vati Rana; Nancy Sahni; Sudip Bhattacharya (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Polycystic ovarian syndrome (PCOS) has now become a common problem among adolescent girls and young women in India. However, little is known about the treatment and satisfaction incurred from it. Our study aimed to assess the treatment-seeking behaviour among patients with PCOS. MATERIALS AND METHODS: The cross-sectional study was carried out in gynecology OPD of PGIMER, Chandigarh. Women with PCOS, 275, visiting the gynecology OPD were included. The treatment-seeking behavior for PCOS was elucidated among cases using a questionnaire. This included parameters like healthcare consulted, preferred system of medicine, referral pattern, treatment efficacy, and expenses incurred. Univariate descriptive analysis was used to present the results. RESULTS: The majority (68%) of the study participants were less than 25 years of age. The average weight was 66.78 (±13.0) Kg. Half of the participants were students. More than 70% belonged to the upper or upper-middle class. The study participants were diagnosed with PCOS at an average age of 21.4 (±4.7) years. The minimum age reported at diagnosis was 11 years, and the maximum age of diagnosis was 36 years. Most respondents preferred Allopathic treatment followed by homeopathy and Ayurveda. Few also opted for other treatment choices like diet therapy, yoga & meditation, weight loss supplements, and home remedies. Treatment efficacy ranged between 17.3%-34.2%. The majority of respondents reported the treatment to be moderately expensive. Most respondents (58.91%) were hardly influenced, while 16% were quite influenced by PCOS medicine or treatment advertisements. CONCLUSION: PCOS patients opt for different treatment options but generally find the treatment less effective and expensive.